LEXICAL EQUIVALENCE IN THE TRANSLATION OF SONG LYRICS “ HANYA RINDU” INTO “JUST MISSING YOU” - Jedho, Fransiska; Hayon, Emanuel B; Bewu, Agnesia; Ranggajatayu, Emanuel; Kobun, Maria Y K (Lantern: Journal of Language and Literature, 2025)
This study aims to explore the application of lexical equivalence in the translation of song lyrics “Hanya Rindu” by Andmesh Kamaleng into “Just Missing You” by Emma Heesters. Using a qualitative approach, this study analyzes how the original meaning and nuance of the lyrics are preserved through the theory of formal and dynamic equivalence proposed by Nida and Taber. The results of this study show that there are 15 data found, where 2 data or 13.33% are formal equivalence and 13 data or 86.67% are dynamic equivalence. From the results of this analysis, the researcher concludes that the dynamic equivalence approach is more dominant than formal equivalence in this translation, this helps English-speaking listeners feel the meaning and nuances of longing even though there are some parts that create ambiguity. This research emphasizes the importance of lexical equivalence so that the translation is not only accurate, but also able to touch the feelings of English-speaking listeners.